PENGARUH PENGGUNAAN CHATGPT, LITERASI DIGITAL DAN MOTIVASI BELAJAR TERHADAP SELF-REGULATED LEARNING MAHASISWA ADMINISTRASI PENDIDIKAN - Kasmiyati, Kasmiyati; Habibi, Akhmad; Wijaya, Hansein Arif (STKIP Pesisir Selatan, 2025)
Objective: This study aims to determine the effect of ChatGPT use, digital literacy, and learning motivation on self-regulated learning (SRL) among students of the Educational Administration Study Program, Jambi University. Methods: This quantitative research employed a survey approach with a total of 188 active students from the Educational Administration Study Program in the 2022–2025 academic year, selected using a simple random sampling technique based on Slovin’s formula with a 5% error rate. The research instrument was a Likert-scale questionnaire tested for validity and reliability. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM–PLS) through SmartPLS 3.0 software. Results: The findings showed that: (1) ChatGPT use had no significant effect on self-regulated learning (p = 0.507; T = 0.664 < 1.96), (2) digital literacy had a positive and significant effect on self-regulated learning (p = 0.000; T = 4.392 > 1.96), and (3) learning motivation had a positive and significant effect on self-regulated learning (p = 0.020; T = 2.326 > 1.96). Simultaneously, ChatGPT use, digital literacy, and learning motivation influenced self-regulated learning with an R² value of 0.363, indicating a moderate category.